A Review of Research into the Phenomenon of Fraud and Abuse in the Modern Economy: The Scale of the Problem and the Prospects for Counteracting - Skoczylas-Tworek, Agnieszka (Journal of Public Governance, 2023)
Objective: The phenomenon of fraud and abuse is currently one of the greatest threats to the effective functioning of organisations. The purpose of this article is to assess the scale of the fraud phenomenon, taking into account the main types of fraud and their perpetrators. The paper also presents the anti-fraud mechanism used by organisations to reduce the risk of fraud and abuse over the past years. Based on the results of the study, conclusions have been formulated.Research Design & Methods: This article uses a combination of quantitative and qualitative methods to describe the development of the phenomenon of fraud and abuse.Findings: The analysis undertaken in the article showed that among anti-fraud controls, the whistleblowing tool has the highest effectiveness. In contrast, among the perpetrators of fraud, the highest percentage is taken by the employees of the organisation. The study also showed the progress of companies in implementing anti-fraud mechanisms when compared to previous years. However, it is still not sufficient enough to effectively reduce the rate of growth of committed fraud and abuse.Implications / Recommendations: The discussion undertaken in the publication around the development of fraud and abuse indicated that the implementation of appropriate control mechanisms is essential to reduce this phenomenon. Technological advances are giving fraudsters much greater opportunities, which means that anti-fraud mechanisms will prove insufficient in the long run. It is, therefore, necessary to better adjust anti-fraud control mechanisms to the organisational structure as well as its level of culture and ethical maturity. This should be accompanied by legal initiatives at the national and international level, such as sanctioning mandatory reporting in this regard by entities.Contribution / Value Added: The phenomenon of fraud and abuse is a significant problem for the development of organisations. Meanwhile, the controls to reduce it are still insufficient. Organisations should put much more emphasis not only on implementing anti-fraud controls, but also on monitoring their effectiveness. Legal support aimed at creating tighter anti-fraud systems is also necessary.